The implications of market liberalization and world price movements for wheat price policy in Sudan - Dorosh, Paul A.; Siddig, Khalid; Kirui, Oliver K. (International Food Policy Research Institute, 2022)
Wheat is an essential commodity in Sudan and a staple for millions. It is second only to sorghum as a key source of calories. The demand for wheat has grown over the last two decades because of a growing population and changing consumer preferences for bread and other wheat products. Domestic farming provides only about 15 percent of the national wheat requirement. The rest is imported mainly from the Black Sea port (Russia and Ukraine). With the Sudanese wheat growing season approaching, this policy brief observes the movement of domestic and international wheat prices and analyzes the possible implications of a reduction in real prices on production, imports, and consumption of wheat products.